Autentisitas Hadis dalam Manuskrip Risalah 73 Golongan pada Koleksi Surau Tarekat Syatariyah Calau Kabupaten Sijunjung - Syukriadi Syukriadi; Novizal Wendri; Ahmad Taufik; Edriagus Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Research on the manuscripts found in the Syatariyah tarekat surau collection in Calau, Sijunjung Regency, West Sumatera Province. ancient manuscripts were not only stored and displayed in one place, but the knowledge contained in them can still be studied and developed and one of them is research. about the manuscripts of the treatises of the seventy-three groups that are stored in the Surau. This research is library research using takhrij hadith. This discussion focuses more on the discussion related to the hadith contained in the treatise manuscripts of 73 groups found in Surau Calau, Sinjunjung Regency and doing takhrij in finding the quality and authenticity of the hadith. In this study, the authors took 3 hadiths contained in the manuscript. From the results of tracking the 3 hadiths, it was found 10 traditions from various hadith and narrators. And after takhrij sanad and matan hadith, it can be concluded, that all hadith chain paths are judged dhaif (mardud) by hadith scholars, except for the hadith path narrated by al-Qadhi al-Maki number 1357, because the hadith is considered hasan by hadith scholars